Efficacy of Epithelium-Off and Epithelium-On Corneal Collagen Cross-Linking in Pediatric Keratoconus - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Objectives: To evaluate the efficacy of riboflavin/ultraviolet A epithelium-off (epi-off) and epithelium-on (epi-on) corneal collagen cross-linking (CXL) in progressive pediatric keratoconus. Methods: Thirty-six eyes of 27 patients aged 18 years or younger (12-18 years) diagnosed with progressive keratoconus and treated with epi-off (n = 18 eyes) or epi-on (n = 18 eyes) CXL were included in this study. All patients were followed up for 24 months postoperatively. Results: At 24-month follow-up, the mean corrected distance visual acuity (CDVA) improved from 0.24 +/- 0.17 to 0.17 +/- 0.11 logMAR in the epi-off group (P=0.032). In the epi-on group, CDVA improved from 0.33 +/- 0.23 to 0.26 +/- 0.20 logMAR (P=0.012), but the improvement was not significantly different between groups (P > 0.05). In the epi-off group, all mean K values improved: K1 (Delta- -20.63 D, P-0.024), K2 (Delta= -20.73 D, P=0.008), and Kmax (Delta= -21.4 D, P=0.035), whereas in the epi-on group, Kmax and K2 did not change significantly and K1 (Delta=0.68 D, P=0.029) significantly worsened. Postoperative mild corneal haze occurred in 5 eyes (28%) in the epi-off group. No postoperative complications were observed in the epi-on group. In 94.4% of the epi-off group, keratoconus regressed (44.4%) or stabilized (50.0%), whereas in the epi-on group, only 66.6% regressed (33.3%) or stabilized (33.3%), and the difference was significant (P=0.038). Conclusions: The efficacy of the epi-on procedure in terms of its ability to halt keratoconus progression appears to be 0.70 of the efficacy of epi-off CXL.
Keywords: Keratoconus; Cross-linking; Children; Pediatric patients; Younger than 18 years; Epithelium-off; Transepithelial; Epithelium-on; Pentacam; HIGHER-ORDER ABERRATIONS; PROGRESSIVE KERATOCONUS; RIBOFLAVIN; CHILDREN